Herbicides Tolerance in a Pseudomonas Strain Is Associated With Metabolic Plasticity of Antioxidative Enzymes Regardless of Selection - Rovida, Amanda Flávia da Silva; Costa, Gessica; Santos, Mariana Inglês; Silva, Caroline Rosa; Freitas, Paloma Nathane Nunes; Oliveira, Elizangela Paz; Pileggi, Sônia Alvim Veiga; Olchanheski, Ricardo Luiz; Pileggi, Marcos (Frontiers in Microbiology, 2021)
Agriculture uses many food production chains, and herbicides participate in this process by eliminating weeds through different biochemical strategies. However, herbicides can affect non-target organisms such as bacteria, which can suffer damage if there is no efficient control of reactive oxygen species. It is not clear, according to the literature, whether the efficiency of this control needs to be selected by the presence of xenobiotics. Thus, the Pseudomonas sp. CMA 6.9 strain, collected from biofilms in an herbicide packaging washing tank, was selected for its tolerance to pesticides and analyzed for activities of different antioxidative enzymes against the herbicides Boral®, absent at the isolation site, and Heat®, present at the site; both herbicides have the same mode of action, the inhibition of the enzyme protoporphyrinogen oxidase. The strain showed tolerance to both herbicides in higher doses than those applied in agriculture. The toxicity of these herbicides, which is greater for Boral®, was assessed by means of oxidative stress indicators, growth kinetics, viability, and amounts of peroxide and malondialdehyde. However, the studied strain showed two characteristic antioxidant response systems for each herbicide: glutathione-s-transferase acting to control malondialdehyde in treatments with Boral®; and catalase, ascorbate peroxidase, and guaiacol peroxidase in the control of peroxide induced by Heat®. It is possible that this modulation of the activity of different enzymes independent of previous selection characterizes a system of metabolic plasticity that may be more general in the adaptation of microorganisms in soil and water environments subjected to chemical contaminants. This is relevant to the impact of pesticides on the diversity and abundance of microbial species as well as a promising line of metabolic studies in microbial consortia for use in bioremediation.